Boron and lithium recovery from aqueous solutions by ion-exchange resin stuffed electro-electrodialysis process with hydrogen production - Ragad F. Alshebli (16855098) (2023)
A considerable amount of lithium is released in the wastes generated during the boron mineral enrichment process. Hence, there is a need to develop systems or processes to recover lithium and boron minerals from the waste of mining industries. In this context, electro-membrane processes have gained importance in literature recently. This study proposes a novel electro-membrane process to recover lithium and boron from an aqueous solution and simultaneous hydrogen production using an electro-electrodialysis stack composed of monovalentanion and monovalent-cation-exchange membranes filled with ion-exchange resins. The effect of the operating parameters, such as current density, flow rate, pH type of ion-exchange resins, and initial conductivity value of the aqueous solution, on the system efficiencies are investigated. Finally, the proposed electrochemical stack’s energy consumption and hydrogen production rates are calculated based on the measurements. The results reflect that maximum conductivity removal efficiency is achieved at 90% by the electro-electrodialysis process with ion-exchange resins. The highest removal efficiency of boron and lithium ions are achieved via electroelectrodialysis with ion-exchange resin as 95.1% and 99.5%, respectively. The hydrogen gas production rate is calculated as 13.55 mmol/h with the same configuration and adding ion-exchange resins to the electroelectrodialysis process improves hydrogen production by 8.6%. Finally, the net energy consumption is calculated as 6.1 kWh/m3 of synthetic wastewater. This study presents a promising method to produce hydrogen and recover valuable minerals of boron and lithium from the aqueous waste solutions. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2023.110687